Work Life Balance dan Tipe Kepemimpinan: Implikasinya pada Motivasi Kerja Karyawan PT. Telkom Witel Gorontalo - Maulana, Alit Tegar; Ahmad, Muchtar; Rahman, Endi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aimed to determine the influence of work-life balance and leadership style on employee work motivation at PT. Telekomunikasi Indonesia (Persero) Gorontalo Region. The data in this study was collected through a questionnaire. The population in this study was 213 employees of PT. Telekomunikasi Indonesia (Persero) Witel Gorontalo. The sample in this study consisted of 68 respondents who were taken through probability sampling using the Slovin formula. The data in this study were analyzed using multiple linear regression tests assisted by the SPSS 22 application. Based on simultaneous tests on the variables, work-life balance and leadership style affected work motivation. Work motivation influenced 38,8% of the result, while other unexamined variables influenced 61,2%.